GW24-e1008 The hypolipidaemic activity of danlou tablet extract in Triton WR-1339 induced hyperlipidaemic rats: A comparison with rosuvastatin. (1st October 2013) - Ruizhen, Ji; Chenghong, Yu; Zhiqing, He; Feng, Wu; Chun, Liang; Zonggui, Wu
Abstract : Objectives: We have studied method of Danlou tables' dynamic effcet on serum cholesterol, triglyceride in experimental acute hyperlipidemia rats. Methods: 48 healthy adult male SD rats were randomly divided into 6 groups: blank control group, model control group, rosuvastatin group, low dose of Danlou tablet group, medial dose of Danlou tablet group, high dose of Danlou tablet group, Continuous administrate drug 14 days later, through tail intravenous Trition- WR1339 and high fat diets, building acute hyperlipidemia rat model, and observe dynamic change of blood lipid index within 48 hour after building model, levels of liver lipid and expression of relevant lipid metabolism genes. Results: administration of high dose Danlou tablet can significantly inhibit an acute rise in serum TC and TG caused by Trition-WR1339 (P < 0.05), but rosuvastatin can not exert lipid-lowering effect fully. Lipid-lowering effect in low or medial dose Danlou tablet group were obviously less than high dose group, and its lipid-lowering effect have obvious dose dependent (P < 0.05); Liver lipid levels in high dose Danlou tablet group was significantly lower than the model control group and the statin group (P < 0.05); For expression of liver acetyl CoA carboxylase (ACC) and cholesterol 7- hydroxylase (CYP7A1), the former in high dose Danlou tablet group was lower than that in model control group and the statin group (P < 0.05), the latter in high dose Danlou tablet group was obviously higher than statin group (P < 0.05). Conclusions: Danlou tablet and relevant traditional Chinese medicine can effectively reduce both plasma cholesterol and triglyceride levels, do not cause liver lipid deposition, and its mechanism may be related to increased expression of liver CYP7A1 and reduce ACC synthesis.